2012
DOI: 10.1026/0049-8637/a000066
|View full text |Cite
|
Sign up to set email alerts
|

Differenzielle Benotungen von Mädchen und Jungen

Abstract: Zusammenfassung. Wir gehen der Frage nach, inwiefern Geschlechtsunterschiede in Noten darauf zurückgeführt werden können, dass Lehrkräfte bei Jungen eine geringere Selbststeuerung im Lernen wahrnehmen als bei Mädchen. Bei 1533 Mädchen und Jungen aus 78 vierten Grundschulklassen wurden Halbjahresnoten für Deutsch und Mathematik, standardisierte Testleistungen im Lesen und in Mathematik sowie Einschätzungen der Selbststeuerung im Lernen durch die Klassenlehrkraft erhoben. In Deutsch konnten die besseren Noten, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
4
9
0
15
Order By: Relevance
“…Our results support the assumption that a gender gap with girls outperforming boys in language-based subjects (here German) as well as in the corresponding SPA (hypotheses 1a and 1b) exists (see also Deary et al, 2007;Hannover & Kessels, 2011;Kuhl & Hannover, 2012;Marsh & Yeung, 1998;Spinath et al, 2010;Weis et al, 2013). For Math performance, no mean differences were found between boys and girls (hypothesis 2a, see also Kuhl & Hannover, 2012;Weis et al, 2013).…”
Section: Mean Differences In Predictor and Criterion Variablessupporting
confidence: 87%
See 1 more Smart Citation
“…Our results support the assumption that a gender gap with girls outperforming boys in language-based subjects (here German) as well as in the corresponding SPA (hypotheses 1a and 1b) exists (see also Deary et al, 2007;Hannover & Kessels, 2011;Kuhl & Hannover, 2012;Marsh & Yeung, 1998;Spinath et al, 2010;Weis et al, 2013). For Math performance, no mean differences were found between boys and girls (hypothesis 2a, see also Kuhl & Hannover, 2012;Weis et al, 2013).…”
Section: Mean Differences In Predictor and Criterion Variablessupporting
confidence: 87%
“…This gender gap has shifted throughout the past decades (Freudenthaler, Spinath, & Neubauer, 2008): Two meta-analyses found only negligible gender differences in the results of standardized Math tests (Else-Quest, Hyde, & Linn, 2010;Hyde, Fennema, & Lamon, 1990) and various studies now consistently show that girls outperform boys in language based subjects (Deary, Strand, Smith, & Fernandes, 2007;Marsh & Yeung, 1998;Spinath, Freudenthaler, & Neubauer, 2010; for an overview on German samples see Hannover & Kessels, 2011). A similar pattern emerged when grades were considered as the achievement criterion: "When differences are found, they almost always favor girls" (Kimball, 1989, p. 199, see also Kuhl & Hannover, 2012;Marsh & Yeung, 1998;Spinath et al, 2010;Weis, Heikamp, & Trommsdorff, 2013). There is still no generally accepted idea, which individual characteristics potentially account for this gender gap.…”
Section: Introductionmentioning
confidence: 53%
“…Past research has shown that besides cognitive abilities (e.g., intelligence; Deary et al, 2007; Spinath et al, 2010) the motivation and ability to self-regulate is positively associated with school achievement (Duckworth and Seligman, 2005; Suchodoletz et al, 2009). In line with these findings, previous studies have indicated that specific components of self-regulation—behavioral regulation or self-regulated learning—could contribute to gender differences in school achievement (Duckworth and Seligman, 2006; Kuhl and Hannover, 2012). However, by only investigating behavior regulation, these previous studies neglected the wider conceptualization of self-regulation.…”
supporting
confidence: 73%
“…In a sample of US-American eighth graders, Duckworth and Seligman (2006) found that girls' higher school achievement can be explained in part by behavior regulation. Kuhl and Hannover (2012) showed that in a sample of German fourth graders, teachers' ratings of children's self-regulated learning could partly explain gender differences in school achievement. Here, we examined both behavior regulation and emotion regulation as aspects of self-regulation.…”
Section: Gender Self-regulation and School Achievementmentioning
confidence: 99%
See 1 more Smart Citation